Implementation on RSA Scheme and Shamir’s Three Pass Scheme with Hill Cipher for data encryption and decryption / Nurr Aida Nor Hisam, Nur Farah Nabilla Nizar and Nur Fatiha Azizah Noorazlan - Nor Hisam, Nurr Aida; Nizar, Nur Farah Nabilla; Noorazlan, Nur Fatiha Azizah (2023)
In today's digital environment, data transmission and storage security and privacy are essential. The RSA scheme, Shamir's Three-Pass Scheme, and the Hill Cipher are three effective cryptographic approaches that are implemented in this study. Using a public private key pair and the RSA scheme, which is based on prime numbers, secure key exchange and data encryption become possible. Shamir's Three-Pass Scheme establishes a shared secret key without the chance of interception through three rounds of communication between sender and recipient. Multiple letters are encrypted simultaneously using the polygraphic substitution cipher known as The Hill Cipher. The proposed approach demonstrates the way of various cryptographic schemes can be used effectively to enable secure communication and the protection of sensitive data. Data encryption using RSA and Hill Cypher, safe key exchange using Shamir's Three-Pass Scheme, and subsequent decryption using the proper schemes provide practical implementation. The purpose of this study is to give some exposure regarding research on the implementation of RSA and Shamir's Three-Pass Scheme with Hill Cipher for Data Encryption and Decryption. In this study, the combined RSA with Shamir's Three-Pass Scheme using a 3x3 matrix is used to generate the encryption on RSA to increase the level of security in data encryption. From the result, the combination with Hill Cipher obtained the final decrypted plaintext, which is the same message sent by the sender. From the implementation that can be done, this study also makes other calculations using different matrix conditions to see if different matrix conditions can be used for the calculation of the combination of these three schemes.